Sistem Informasi Penjualan PT Surya Multi Cipta - Kumbang, Ari; Kusumawati, Arie (Institut Teknologi dan Bisnis Kalbis, 2019)
PT Surya Multi Cipta is a company engaged in manufacturing machine. Sales process at PT Surya Multi Cipta still rely on Microsoft Office and Excel for recording sales and other data. Reporting process is often hampered due to the data must be searched manually, so that required sales information system. The purpose of research is to build information systems sales of PT. Surya Multi Cipta to solve systematic sales and report problems. The method used by researcher to make sales information system is System Development Life Cycle (SDLC) with prototype method and system modeling using Unified Modeling Language (UML). Sales information system created using laravel framework and programming language PHP, JavaScript and MySQL database. The results of this research is a websitebased sales information system that helps in the process of selling. Based on the results of testing and evaluation of researchers, sales information system is able to help the business process running.